Indian judiciary and challenges of 21st century - Anand, A.S. (1999)
Tracing (since independence) unfolding of the role of Supreme Court of India and widening of the coverage to include varied aspects of rights and interests of human life and conflict arising therefrom the author justifies courts' power of judicial review as envisaged under `judicial activism'. He then deals with several challenges which the Indian judicial system will have to handle in the future and gives useful suggestions to sort these out effectively through enlisting unstinted cooperation from other players in the system. - Reproduced
Keywords: Judiciary - India; Judiciary